2016
DOI: 10.5565/rev/elcvia.826
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Angular Texture Pattern (ATP) Extraction Method for Crop and Weed Discrimination Using Curvelet Transformation

Abstract: Weed management is the most significant process in the agricultural applications to improve the crop productivity rate and reduce the herbicide application cost. Existing weed detection techniques does not yield better performance due to the complex background and illumination variation. Hence, there arises a need for the development of effective weed identification technique. To overcome this drawback, this paper proposes a novel Angular Texture Pattern (ATP) Extraction Method for crop and weed discrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…One may wonder how these classification results compare toward the literature on weed detection in less dense culture cited in the introduction section [12][13][14][15][16][17][18][19][20][21]. The performance in this literature varies from 75% to 99% of good detection of weed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One may wonder how these classification results compare toward the literature on weed detection in less dense culture cited in the introduction section [12][13][14][15][16][17][18][19][20][21]. The performance in this literature varies from 75% to 99% of good detection of weed.…”
Section: Discussionmentioning
confidence: 93%
“…Bayesian classifier was used in [16] for plant and weed discrimination. Shape, texture features [12,[17][18][19] or wavelet transform [20,21] coupled with various classifiers including support vector machine (SVM), relevance vector machine (RVM), fuzzy classifier, or random forests were also shown to provide successful pipelines to discriminate between plant and weeds.…”
Section: Introductionmentioning
confidence: 99%
“…A screening and elimination of unnecessary features is essential to reduce feature quantity and increase data processing speed. Different types of algorithms have been utilized to select effective features for orchard management, including stepwise discriminant analysis [ 68 ], quadratic discriminant analysis [ 69 ], linear discriminant analysis [ 70 ], hybrid artificial neural networks-cultural algorithm (ANN-CA) [ 71 ], particle swarm optimization (PSO) based differential evolution method [ 72 ], kernel principal component analysis (KPCA) [ 73 ], and so on. Upon locating/accessing the target to be sprayed, spray volume at the nozzle is adjusted based on the size or quantity of the target present in the images captured from the orchards.…”
Section: Core Components and Technologies For Precision Sprayingmentioning
confidence: 99%
“…In the learning-based approaches, both unsupervised and supervised machine learning algorithms were investigated for vegetation segmentation. In the literature as unsupervised methods that do not require any training phase, K-means clustering (Kumar & Prema, 2016); Prema & Murugan, 2016) and particle swarm optimization (PSO) based K-means clustering (PSO) (Bai et al, 2014) can be found. As supervised methods that previously require a training phase, decision trees (Guo, Rage, & Ninomiya, 2013;Riegler-Nurscher, Prankl, Bauer, Strauss, & Prankl, 2018) artificial neural networks (Potena, Nardi, & Pretto, 2017) and statistical based (Ruiz-Ruiz, Gómez-Gil, & Navas-Gracia, 2009;Zheng, Shi, & Zhang, 2010) methods can be found.…”
Section: Introductionmentioning
confidence: 99%